(untitled) (International Journal of Engineering and Computer Science, 2016)
The abstract of this paper discusses the wireless sensor network which is a modernistic addition in the fields of radio networks and also provides new applications with a new prototype for sensing and broadcasting information from various environments with potential to serve many and desired applications at very low cost. In wireless sensor network, a collection of small sensor nodes communicates through radio interface. Due to the requirement of low device complexity with low energy consumption a balanced communication and signal or data processing capabilities must be found.